196 Functional high-throughput screening identifies microrna-26b as pro-survival and angiogeneic factor for endothelial cells. (5th June 2017) - Mellis, David; Rose, Lorraine; Martello, Andrea; Al-Haj Zen, Ayman; Caporali, Andrea
Abstract : Critical limb ischaemia (CLI) is a serious form of peripheral artery disease where patients suffer from reduced arterial blood flow and subsequent loss of tissue viability. Therapeutic angiogenesis uses pro-angiogenic factors to stimulate new blood vessels formation to bypass existing blockages. Despite promising pre-clinical data, the outcome of clinical trials using single proangiogenic growth factors remains inconclusive. MicroRNAs (miRNAs) are small non-coding RNAs that orchestrate genetic networks by modulating simultaneous gene expression, thus suitable for therapeutic regulation of post-ischaemic angiogenesis. The aim of this study is to identify novel miRNAs that can influence vascular endothelial cells (EC) function and identify their relevant target genes. High content screening (HCS) of human miRNA mimic library is an emerging approach that utilises robotic microscopy platforms along with unbiased image analysis algorithms to generate quantitative data. Therefore, we used HCS to identify miRNAs that regulate EC proliferation and establish their potential as a therapeutic target for CLI. High throughput screening of over 1500 unique microRNA mimics revealed miR-26b as a top candidate for regulating EC functions. The overexpression of miR-26b significantly increased the proliferation and migration of ECs. Furthermore, it increased cell survival and importantly enhanced EC tube formation and branching morphogenesis. Stimulating ECs with the growth factor VEGFA increased EC proliferation associated with increased miR-26b expression. Expression analysis revealed an increase in endothelial cell tip enrichment genes including FLT4, ESM1, Ang-2 and PDGFB in EC overexpressing miR-26b. In-vivo, Q-PCR analysis confirmed an increase level of miR-26b expression in EC sorted form limb muscles 3 days post-ischaemia. Furthermore, we tested the effects on in vivo angiogenesis using the Matrigel implant model. Histological analysis at day 10 with the implants confirmed miR-26b mimics increased the vessel density. After confirming the important pro-survival and pro-angiogenic role miR-26b has in ECs, we used HCS to identify downstream target genes. We found that Phosphatase and Tensin homolog (PTEN) and phosphatase gene PPP2R2A are direct targets of miR-26b and their regulation determined the phenotype of miR-26b in ECs. MicroRNA-26b was for the first time identified as a pro-survival and pro-angiogenic factor for EC by the use of novel HCS techniques. We believe miR-26b is an excellent therapeutic target for the treatment of CLI and we continue to investigate and characterise its role in post-ischaemic angiogenesis.